1982
DOI: 10.1016/0014-5793(82)80936-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of two variants of native one‐chain tissue plasminogen activator

Abstract: The native one-chain tissue plasminogen activator from the human melanoma cell line (Bowes) occurs in two variants as demonstrated by sodium dodecylsulphate-polyacrylamide gel electrophoresis of reduced and carboxymethylated samples. The two variants were isolated by affinity chromatography on arginineSepharose using a guanidinium-HC1 gradient, in the order of elution, the variants were designated tissue plasminogen activator I and II. Variant I was found to be 3000 Mr larger than variant II and the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 13 publications
1
21
1
1
Order By: Relevance
“…1). The structural background for this additional heterogeneity is unknown, but forms corresponding to the two types can be separated [27] and may possibly be derived from carbohydrate differences, A heterogeneity due to a partial plasmic digestion of the C-terminal part of the chain cannot be fully excluded, but there are no indications of a 3-kDa fragment in the digest. Methodologically, it may be noticed that the mixtures are interpretable by direct sequence analyses, in the same way as some other N-terminal heterogeneities [28] and limited peptide bond cleavages [18] have been determined.…”
Section: Structural Analysismentioning
confidence: 99%
“…1). The structural background for this additional heterogeneity is unknown, but forms corresponding to the two types can be separated [27] and may possibly be derived from carbohydrate differences, A heterogeneity due to a partial plasmic digestion of the C-terminal part of the chain cannot be fully excluded, but there are no indications of a 3-kDa fragment in the digest. Methodologically, it may be noticed that the mixtures are interpretable by direct sequence analyses, in the same way as some other N-terminal heterogeneities [28] and limited peptide bond cleavages [18] have been determined.…”
Section: Structural Analysismentioning
confidence: 99%
“…Interestingly, some investigators have observed tPA size heterogeneity [16][17][18][19][20]. One interpretation of these observations is that the lower molecular mass tPA molecules are the result of partial proteolysis, perhaps by plasmin, during extraction.…”
Section: Introductionmentioning
confidence: 99%
“…There is first, as described above, the single-chain form which can be converted into a double-chain form. Secondly, both the single-chain and the double-chain molecule may occur in two forms, the molecular weight of which differs by about 3,000 daltons, but with similar enzymatic activity [ 17,18]. It has been shown that the molecule of 63.000 daltons is glycosylated at positions 118, 186 and 448, while the molecule of 60.000 daltons is glycosylated only at posi tions 118 and 448 [18].…”
Section: Physicochemical Properties Of T-pamentioning
confidence: 99%